Settling a conflict of interest in judicial and lawyer activity: general and specific issues (by the example of class proceedings) - O. S. Belosludtsev; I. V. Ginzburg (Russian Journal of Economics and Law)
Objective: to clarify the concept of “conflict of interest”, to identify the peculiarities of conflict of interest resolution in group proceedings, and to develop practical recommendations to prevent conflict of interest in judicial and advocacy activities.Methods: dialectical approach to cognition of social phenomena, allowing to analyze them in historical development and functioning in the context of the totality of objective and subjective factors, which predetermined the following research methods: formal-logical and comparative-legal.Results: the objective impossibility of legislatively stipulating all possible variants of conflicts of interest makes it necessary to resolve both “real” and “seeming” conflicts of interest directly by the law enforcer. The lack of appropriate rules and recommendations causes uncertainty regarding the presence (absence) of a judge’s conflict of interest. The article formulates the main signs of a conflict of interest: a) a contradiction between the personal (private) interests of a judge and the principles of justice; b) personal interest of a judge; c) financial interest of a judge; d) the existence of a legal fact confirming the conflict of interest; e) the need to inform the persons involved in the case about the conflict of interest; f) the burden of proving the grounds for recusal lies with the applicant. In addition, the author provides a legal assessment of the measures of settling a conflict of interest in judicial activity, outlines approaches and proposals to improve the institute of conflict of interest settlement in judicial and advocacy activities, and reveals the peculiarities of conflict of interest settlement in group proceedings.Scientific novelty: the article presents a comprehensive study of the institute of conflict of interest in judicial and advocacy activities, in which the main features of conflict of interest in judicial and advocacy activities are identified, the peculiarities of conflict of interest settlement in proceedings for the protection of rights and legitimate interests of a group of persons are determined, a comparative legal analysis of foreign and Russian law enforcement practice on the conflicts of interest settlement is carried out.Practical significance: the main conclusions of the article can be used in law-making activities to improve the legal regulation of the conflict of interest institute. The formulated provisions and conclusions can be used in lectures, seminars, preparation of methodological materials on legal disciplines.